IMPACT OF THE WAR ON THE ECONOMY OF UKRAINE: MACROECONOMIC ASPECT - Rosola , U.V.; Hladynets , N.Yu.; Petrichko , M. M. (The actual problems of regional economy development, 2023)
The article examines the current state of the main macroeconomic indicators of Ukraine. The purpose of the scientific work is the study of modern trends of the main macroeconomic indicators: the level of GDP, the level of unemployment and inflation, changes in tax legislation, analysis of the main international food agreements in the conditions of war. Their impact on the country's economy and the functioning of business in the current conditions is studied. Scientific articles of domestic and foreign scientists were used for the research. To achieve the goal, such scientific methods as: analysis and synthesis, induction and deduction, economic-statistical and generalization were used. As a result of the analysis, it was established that the war in Ukraine has a significant impact on the functioning of domestic enterprises and business as a whole. It has been investigated that one of the key tasks of the Ministry of Economy is the relocation of enterprises from temporarily occupied territories to safer regions - Lviv, Transcarpathia, Volyn, Chernivtsi and other regions. Naturally, thanks to this process, tax revenues are paid to the budget of various levels, existing jobs are maintained, and new personnel, which are in short supply, are recruited. It has been established that powerful missile strikes on critical infrastructure, rising inflation, unemployment, Ukraine's inability to carry out full-fledged international trade by sea make the stability and development of the economy impossible. The largest external donors of financial assistance to Ukraine are analyzed in detail. The negative impact of military operations on the size of Ukraine's exports and imports was revealed. It is noted that the energy infrastructure is constantly exposed to shelling, and thus to the temporary destabilization of Ukrainian business as a whole. Solving existing problems is possible by carrying out certain measures: provision of financial assistance by foreign countries and funds, development of energy sources, formation of alternative potential in the energy sector, free movement of capital and labor resources. In general, this will provide an opportunity to rebuild the domestic economy according to European principles.